PSMA-targeted therapy for non-prostate cancers - Wang, Jarey H.; Kiess, Ana P. (Frontiers in Oncology, 2023)
Radioligand therapy (RLT) agents are demonstrating a crucial role in the clinical approach to aggressive malignancies such as metastatic castrate-resistant prostate cancer (m-CRPC). With the recent FDA approval of prostate-specific membrane antigen (PSMA)-targeted RLT for m-CRPC, the field has broadened its gaze to explore other cancers that express PSMA in the tumor parenchyma or tumor neovasculature. In this review article, we discuss current progress in the clinical use of PSMA RLTs in non-prostate cancers such salivary gland cancers, renal cell carcinoma, high grade glioma, and soft tissue sarcoma. We highlight early reports in small case series and clinical trials indicating promise for PSMAtargeted RLT and highlighting the importance of identifying patient cohorts who may most benefit from these interventions. Further study is indicated in non-prostate cancers investigating PSMA RLT dosimetry, PSMA PET/CT imaging as a biomarker, and assessing PSMA RLT safety and efficacy in these cancers.